Fun with educational games: exploring students' intrinsic motivation - Mohd Ayub, Ahmad Fauzi; Wan Jaafar, Wan Marzuki; Yahaya, Faizal; Wong, Su Luan (Malaysian Educational Technology Association, 2007)
Technology is emerging as a great tool to use within classrooms. It is an essential tool in the teaching and learning environment for mathematics as it can influence the way mathematics are taught. Educational games can be a powerful learning tool because of its interactive and multimedia capabilities. Educational games also have the capability to keep students motivated, active and engaged in the teaching learning process. The purpose of this study was to determine the effects of educational mathematics games on students’ motivation. The sample was 69 diploma students who registered for a calculus course. The students were exposed to a three-hour game session related to the subject, calculus. Three dimensions were measured – students’ enjoyment, perceived usefulness and competence with educational games. The results showed that all students enjoyed themselves and felt competent with the educational mathematics games. Students also believed that playing educational mathematics games is useful in improving their mastery of calculus.